Experiences of menstrual inequity and menstrual health among women and people who menstruate in the Barcelona area (Spain): a qualitative study - Anna Sofie Holst; Constanza Jacques‐Aviñó; Anna Berenguera; Diana Pinzón-Sanabria; Carme Valls-Llobet; Jordina Munrós-Feliu; Cristina Martínez-Bueno; Tomás López‐Jiménez; Ma Mercedes Vicente‐Hernández; Laura Medina‐Perucha (2022)
Menstrual health and menstrual inequity have been neglected in social, economic, healthcare and political spheres. Although available evidence is scarce, it already suggests a link between experiencing menstrual inequity (which refers to the systematic disparities in accessing menstrual health and education, menstrual products and spaces for menstrual management, among other aspects) and menstrual health outcomes. The aim of this study was to explore experiences of menstrual health and menstrual inequity among women and people who menstruate aged 18-55 in Barcelona and surrounding areas (Spain).